Combating Industrial Pollution in the Russian Empire: Legal Context (1800—1917) - A. V. Vinogradov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The article is devoted to the consideration of the Russian pre-revolutionary legislation regulating the control over industrial pollution of the environment. The early Russian sanitary legislation and features of its development in the XIX — early XX centuries are analyzed. Particular attention is paid to the positions of various social groups on the issues of state and public control over the sanitary state of industrial enterprises. It is shown that the first norms prohibiting water and air pollution appeared already at the beginning of the 19th century. The author notes that although they did not contain clear criteria and measures for eliminating pollution, this was typical of many European countries during the study period. As the range of studied sources and literature shows, active work on the development of comprehensive measures against industrial pollution began in the 1890s and continued until the revolution: it did not bring practical results in the legal field, but contributed to a significant deepening of scientific understanding of the environment. The author concludes that, despite the revolutionary events of 1917, the pre-revolutionary experience in combating environmental pollution had a significant impact on the development of Soviet environmental policy.